A Rare Edition of Angelo Poliziano’s Nutricia - Alejandro Coroleu (Translat Library, 2022)
The purpose of this note is to draw scholars’ attention to a little-known edition of Angelo Poliziano’s Nutricia (Leipzig, 1517). One of the only two surviving copies of the volume (Copenhagen, Kongelige Bibliotek, 76, 39) contains annotations which constitute indisputable proof of how Poliziano’s poems attracted the interest of Renaissance readers.
Keywords: Italian humanism; Latin poetry; Angelo Poliziano; Italian and German printers; Marginalia; Hieronymus Adam